2013
DOI: 10.1371/journal.pone.0068281
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Treatment Improves Neuron Viability in an In Vitro Model of Stroke

Abstract: Ischemic stroke is the leading cause of serious, long-term adult disability and is associated with sensorimotor and cognitive impairments due to neuronal degeneration. Currently, recombinant tissue plasminogen activator (rTPA) is the only FDA-approved medical therapy for treatment of patients with acute ischemic stroke. However, rTPA can only be given within 3 hours of symptom onset, and only 2% of patients are eligible. Therefore, there is an urgent need for novel neuroprotective treatment options for ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…Recent studies have demonstrated that the activation of NF-jB and p38MAPK is linked to the pathogenesis of cerebral ischemia Wang et al 2010). Other research reports have shown that mTOR pathway, as a novel neuroprotectants for IS, plays a pivotal role in protecting against stroke (Xiong et al 2014;Fletcher et al 2013). Our findings indicated that the target genes of these differentially expressed miRNAs might participate in the mTOR, MAPK, and ErB signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the activation of NF-jB and p38MAPK is linked to the pathogenesis of cerebral ischemia Wang et al 2010). Other research reports have shown that mTOR pathway, as a novel neuroprotectants for IS, plays a pivotal role in protecting against stroke (Xiong et al 2014;Fletcher et al 2013). Our findings indicated that the target genes of these differentially expressed miRNAs might participate in the mTOR, MAPK, and ErB signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Both damaged/stressed neurons and reactive astrocytes quickly initiate post-ischemic inflammation, through producing pro-inflammatory mediators and educating microglia (43, 69, 70). Rapamycin protects neurons after stroke (12, 71) and inhibits reactive astrocytes (72, 73), thus probably preventing the onset of acute neuroinflammation. Hence, the neuroinflammation might have been alleviated even before Tregs entered the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that mTOR signaling plays an important role in the modulation of both innate and adaptive immune responses (9). In experimental stroke, rapamycin administration 1 hour after focal ischemia ameliorated motor impairment in adult rats (10) and in neonatal rats (11) and improves neuron viability in an in vitro model of stroke (12). However, the mechanisms underlying mTOR-mediated neuroprotection in stroke are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, mixed neuronal cultures that were exposed to oxygen-glucose deprivation and hypoxic post-conditioning, rapamycin exacerbated neuronal death and abolished the protective effects of hypoxic post-conditioning 123 . By contrast, inhibition of autophagy has been demonstrated to prevent mTOR activation in cortical neurons and improve cell survival following oxygen-glucose deprivation 124 .…”
Section: Hypoxia-ischaemiamentioning
confidence: 99%